Role Development of Nurse Managers in The Changing Health Care Practice - Joel Rey Ugsang Acob; Wiwin Martiningsih (STIKes Patria Husada Blitar, 2018)
Rapid changes in today’s healthcare industry are reshaping nurses’ role. The emergence of new healthcare system, the shift from service to business orientations, and extensive redesign of workplace affects the where and how nursing care is delivered as well as those who delivered the care. In the Philippines, healthcare system is in the midst of dramatic evolvement- the devolution of hospitals to LGUs, free healthcare for senior citizens and no balance billing policy yielding to increased client-nurse ratio. These impacts change the roles of nurse managers and their practice. The study aimed to understand the experience and phenomena of nurse managers, their roles in the dynamics of healthcare practice, and seek ways to enhance the development of these roles. The study used descriptive phenomenology-qualitative design, and utilized Colaizzi method during data analyses. Through researcher-made guide questions, the study employed purposively nurse managers as key informants from tertiary hospitals that experienced devolution using the inclusion and exclusion criteria. The researchers conducted interviews with audio- tapes that then later transcribed. The study revealed that nurse managers encountered challenges in the workplace like deprivation of responsibility, less administrative support that challenged their responsibili- ties. The nurse managers identified new roles that they have developed over time like Carative-managerial role, responsibility to educate and the responsibility to the nursing profession. They are believers that the enhancement of such roles is realized through rest and recreation among staffs to avoid burnout and exhaustion, acquiring continuing professional education, clinical teaching and mentoring skills strategies to understand better human behavior. The researchers recommends consumption of such study findings as basis for improving hospital facilities for the provision of patient safety, revisiting and strengthening the hiring and screening policies for new nurses, administrative support for staff development and as basis to conduct further studies on the emerging roles to other settings.